Factors associated with adherence to medication among depressed patients from Saudi Arabia: a cross-sectional study - Jumah, Khalaf Al; Hassali, Mohamed Azmi; Qhatani, Dalal Al; Tahir, Kamal El (Dove Medical Press, 2014)
Background: Several studies have investigated the factors associated with adherence to antidepressants, with inconsistent conclusions. However, no similar study has investigated this issue among patients diagnosed with major depressive disorder in Saudi Arabia. The aim of this study is to explore patients’ adherence to antidepressant medications, and the factors associated with adherence. Methods: A non-experimental cross-sectional design was used to measure adherence to antidepressants among major depressive disorder patients, and the factors associated with adherence. The patients were recruited from the outpatient clinic at the Al-Amal Complex for Mental Health in Riyadh, Saudi Arabia, between August 2013 and January 2014. Eligible participants met with one of the research coordinators for assessment of their adherence. Adherence was investigated indirectly by use of the Morisky Medication Adherence Scale, and patients’ beliefs were assessed through the Beliefs about Medicine Questionnaire. Information about the severity of their depression, demographics, and other study variables were collected. Results: A total of 403 patients met the inclusion criteria and participated in the study. Of those, 203 (50.37%) were females, while the remaining 200 (49.6%) were males. There was an average age of 39 years (standard deviation, ±11 years). Half of the patients (52.9%) reported low adherence to their antidepressant medication, with statistically significant differences between the low adherence and high adherence scores relating to sex, age, and duration of illness. Conclusion: Low medication adherence is a common problem among major depressive disorder patients in Saudi Arabia. Medication-taking behavior among depressed patients is influenced by several factors, mainly patients’ beliefs regarding antidepressants. This study has improved the understanding of the factors associated with adherence to antidepressants.